2012
DOI: 10.3800/pbr.7.64
|View full text |Cite
|
Sign up to set email alerts
|

Interannual and latitudinal changes in zooplankton abundance, biomass and size composition along a central North Pacific transect during summer: analyses with an Optical Plankton Counter

Abstract: 2 but the differences between the three oceanic domains were not significant. However, highly significant latitudinal changes were observed in the mean zooplankton biomass, which ranged from 1.44 to 13.2 mg dry mass m 2 with higher values in the Transitional Domain (TR) than in the Subarctic and Subtropical Domains. The high biomass in the TR was caused by the dominance of large-sized zooplankton with equivalent spherical diameters (ESD) of 2-4 mm, regarded to consist mainly of Neocalanus spp. C5. Both the slo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 31 publications
3
9
0
Order By: Relevance
“…Table 3 summarizes regressions between the OPC-derived mass and directly measured mass, ranges of zooplankton abundance, and biovolume from previous studies. The OPCderived masses were 1.05 to 1.18 times the directly measured mass in previous studies (Yokoi et al 2008;Matsuno and Yamaguchi 2010;Fukuda et al 2012). In this study, the zooplankton biovolume estimated by OPC was 0.95 times the directly measured mass (Figure 3).…”
Section: Opc Measurementssupporting
confidence: 56%
See 2 more Smart Citations
“…Table 3 summarizes regressions between the OPC-derived mass and directly measured mass, ranges of zooplankton abundance, and biovolume from previous studies. The OPCderived masses were 1.05 to 1.18 times the directly measured mass in previous studies (Yokoi et al 2008;Matsuno and Yamaguchi 2010;Fukuda et al 2012). In this study, the zooplankton biovolume estimated by OPC was 0.95 times the directly measured mass (Figure 3).…”
Section: Opc Measurementssupporting
confidence: 56%
“…In May, group C, which is characterized by a high biovolume and dominance of the 2 to 3 mm ESD size class, dominated; however, this changed to other groups during July to August (Figure 6). The 2 to 3 mm ESD zooplankton in this region corresponded with the C5 stages of large copepods Neocalanus spp., and their importance has been reported in previous OPC studies (Yokoi et al 2008;Matsuno and Yamaguchi 2010;Fukuda et al 2012). Along the 155°E line, group C was dominated by the 2 to 3 mm ESD size class and was characterized by a high biovolume during May and at the northern stations from July to August.…”
Section: Temporal Changesmentioning
confidence: 65%
See 1 more Smart Citation
“…Other north/south transects in the North Pacific indicated that zooplankton abundance is lower at low latitudes and is higher at high latitudes (Yokoi et al, 2008;Matsuno and Yamaguchi, 2010;Saito et al, 2011;Fukuda et al, 2012). Where the zooplankton abundance is the lowest, the number of species and species diversity are reported to be higher in the subtropical and tropical oceans for various zooplankton taxa, i.e., Copepoda (Heinrich, 1969), Euphausiacea, Pteropoda and Chaetognatha (Fager and McGowan, 1963).…”
Section: Abundancementioning
confidence: 93%
“…Most studies of heterotrophic biomass or production patterns in the open ocean focus almost exclusively on the top 250 m of the water column (Sabates et al, 1989;Brodeur and Ware, 1992;Mackas, 1995;Brodeur et al, 1996;Young et al, 1996;Sugimoto and Tadokoro, 1997;Goldblatt et al, 1999;Nagasawa, 2000a, b;Uye et al, 2000;Stock and Dunne, 2010;Fukuda et al, 2012;Huo et al, 2012). Much of this research is based on the assumption that virtually all heterotrophic production in the open ocean is derived from top-down nutrient input and, therefore, only the organisms which are migrating above thermocline depth have direct access to nutrition from primary producers.…”
Section: Introductionmentioning
confidence: 99%